2019
DOI: 10.3390/app10010250
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Industrial Wastes and Their Mixtures and Stability of Embankments Made of These Materials

Abstract: The paper presents the results of research on the influence of compaction on the shear strength of fly ash, unburnt and burnt coal wastes, and a composite (a mixture of unburnt coal waste and 30% of fly ash). The tests were carried out in a triaxial compression apparatus on samples with a diameter and height of 10 and 20 cm, respectively. In order to verify usability of the tested waste materials for earthworks, stability calculations of the road embankment made of these materials were carried out. It was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Many examples have been developed to valorise, reuse, dispose, and recycle these solid wastes in many fields including, construction and building materials. For example, Gruchot et al [8] showed the influence of compaction on the shear strength of unburnt and burnt coal wastes without/with fly ash (FA) using triaxial compression tests. The tests and the stability calculations showed that the tested waste materials are useful for earth construction purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Many examples have been developed to valorise, reuse, dispose, and recycle these solid wastes in many fields including, construction and building materials. For example, Gruchot et al [8] showed the influence of compaction on the shear strength of unburnt and burnt coal wastes without/with fly ash (FA) using triaxial compression tests. The tests and the stability calculations showed that the tested waste materials are useful for earth construction purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The high values of the factor of safety obtained may be due to the high values of the shear strength parameters and, above all, cohesion, which were generally high (greater than 40 kPa). The problem arising from the use of such high cohesion values in the calculations was pointed out by Gruchot and Zydroń [30], indicating the need to reduce this parameter in the case of anthropogenic soils by up to 50%. The results of the calculations also indicate that using the shear strength parameters from the tests at 1.0, and 0.05 mm•min −1 , higher values of the factor of safety at the loading of the embankment crest were obtained, which may also be due to the reinforcement of the embankment during its deformation.…”
Section: Stability Calculations Results and Discussionmentioning
confidence: 99%